Lo hipomnémico y protésico de los archivos. Una lectura de "La operación historiográfica". - NAVA MURCIA, Ricardo (Chasqui (13901079))
This essay develops some reflections on the work of the historian, based on a reading of the text "The historiographical operation" by Michel de Certeau. What does this work bring into play when we approach it from alternative interpretive frameworks? Having other tools to interpret it differently allows us to reactivate this historian's thought within another network of meaning, to observe aspects that lie in the background of the practice of history. The instruments I want to employ here are the semantics of two concepts developed by Jacques Derrida in his book Archive Fever, regarding its conceptualization and its technical, external, and inscriptive nature: the hypomnesic and the prosthetic.